Mental Health Differences in Healthcare Workers Exposed to Different Risks During the Coronavirus Disease 2019 Pandemic - Zhang, Yihui; Li, Da; Ouyang, Xuan; Bai, Hanping; Zhao, Linlin; Shi, Yongyan; Tan, Liwen (Frontiers in Psychiatry, 2022)
Abstract Background: The coronavirus disease 2019 (COVID-19) pandemic has caused a significant impact on the physical and mental health of healthcare workers. This study assessed the psychological status of healthcare workers who were exposed to different risk-levels in China and explored the factors that affected their mental health. Methods: Demographic, occupational characteristics, and mental health measurements were collected from 810 workers in 41 hospitals in China, through online questionnaires from February 11 to March 3, 2020. The degree of symptoms for fatigue, anxiety, and insomnia were assessed using the Chinese versions of the Fatigue Severity Scale, 7-item Generalized Anxiety Disorder Scale, and Insomnia Severity Index, respectively. Binary logistic regression analysis was performed to identify factors associated with mental health symptoms. Results: All 810 participants completed the relevant questionnaires without missing data. The prevalence of fatigue, anxiety, and insomnia symptoms was 74.3%, 73.7%, and 61.7%, respectively. Nurses, women, and workers exposed to high-risk areas were more likely to report mental health problems (P < 0.05). After controlling for confounders, exposure to high-risk areas was independently associated with increased symptoms of fatigue, anxiety, and insomnia (fatigue among high-risk areas: OR, 3.87; 95% CI, 2.26 ̶ 6.61; P < 0.001; anxiety among high-risk areas: OR, 2.66; 95% CI, 1.58 ̶ 4.51; P < 0.001; insomnia among high-risk areas: OR, 2.83; 95% CI, 1.68 ̶ 4.79, P < 0.001). Conclusion: The study demonstrated significant differences in psychological symptoms among healthcare workers exposed to different levels of risk, and those in high-risk areas were more vulnerable to experiencing mental health symptoms. These findings emphasize the importance of giving due attention to healthcare workers, especially women, nurses, and those working in high-risk settings during the COVID-19 pandemic.